Exploring the Role of Accounting Information Systems in Improving Operational Efficiency and Financial Reporting Accuracy: A Qualitative Study of Beauty MSMEs in Gorontalo - Zumran Ibrahim; Savira Ramadhani Mokodongan; Natalia Isabel Wantah; Frety Arta Melia Botutihe; Inayah Helingo; Mega Nurannisa Hippy (Review: Journal of Multidisciplinary in Social Sciences, 2026)
This study aims to analyze the implementation of Accounting Information Systems (AIS) in two MSMEs, namely Ggehijaband SASHOP, and evaluate their impact on operational efficiency and financial statement accuracy. Both SMEs have transitioned from manual recording to using AIS applications, such as Qasir, which helps improve transaction processes and inventory management. The results show that AIS can reduce service time from an estimated 10-20 minutes to 2-5 minutes, decrease the workload of cashiers, and improve inventory management consistency. Additionally, SIA has been proven to improve the accuracy of financial reports by reducing pricing errors, COGS calculation errors, and errors in manual transaction recapitulation. Overall, the implementation of AIS has made a positive contribution to business sustainability by improving the effectiveness of internal controls and the quality of information used in decision-making and contributes academically by providing empirical evidence on AIS adoption in MSMEs within a developing economy context.